Vacuum energy as a c-function for theories with dynamically generated masses - Aguilar, A. C.; Doff, A.; Natale, Adriano Antonio [UNESP] (Elsevier B.V., 2011)
We argue that in asymptotically free non-Abelian gauge theories possessing the phenomenon of dynamical mass generation the beta function is negative up to a value of the coupling constant that corresponds to a non-trivial fixed point, in agreement with recent AdS/QCD analysis. This fixed point happens at the minimum of the vacuum energy (Omega), which, as a characteristic of theories with dynamical mass generation, has the properties of a c-function. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: c-function; Dynamical mass generation; Infrared fixed point; Vacuum energy